2019
DOI: 10.1038/s41598-018-37327-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride Doping in Laponite Nanoplatelets on Osteogenic Differentiation of Human Dental Follicle Stem Cells (hDFSCs)

Abstract: Bioactive nanosilicates are emerging prominent next generation biomaterials due to their intrinsic functional properties such as advanced biochemical and biophysical cues. Recent studies show interesting dose-dependent effect of fluoride ions on the stem cells. Despite of interesting properties of fluoride ions as well as nanosilicate, there is no reported literature on the effect of fluoride-doped nanosilicates on stem cells. We have systematically evaluated the interaction of fluoride nanosilicate platelets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…Previous studies have shown that the effect of fluoride ions on stem cells is dosedependent. [102,103] The toxicity of fluoride ions and their effects on differentiation of human dental follicle stem cells were inves-tigated using nano silicate platelets in the presence or absence of fluoride ions. Results of bone regeneration indicated that nanosilicate platelets doped with fluoride enhanced osteogenic cell differentiation compared with platelets that did not contain fluoride ions.…”
Section: Fluoride Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the effect of fluoride ions on stem cells is dosedependent. [102,103] The toxicity of fluoride ions and their effects on differentiation of human dental follicle stem cells were inves-tigated using nano silicate platelets in the presence or absence of fluoride ions. Results of bone regeneration indicated that nanosilicate platelets doped with fluoride enhanced osteogenic cell differentiation compared with platelets that did not contain fluoride ions.…”
Section: Fluoride Deliverymentioning
confidence: 99%
“…Results of bone regeneration indicated that nanosilicate platelets doped with fluoride enhanced osteogenic cell differentiation compared with platelets that did not contain fluoride ions. [ 104 ] In another study, the effect of low‐level sodium fluoride on bone marrow mesenchymal stem cells was evaluated for the extent of wound healing and stem cell differentiation into osteoblasts after traumatic dental injury. The results indicated that 50 µ m of sodium fluoride induced cell motility after 12 h stimulated osteoblast differentiation after 21 days.…”
Section: Ion Deliverymentioning
confidence: 99%
“…To sum up, our study supported the notion that miR-214-3p could inhibit osteogenic differentiation of AS fibroblasts by targeting BMP2 and blocking the BMP-TGFb axis, highlighting promising novel approaches for AS treatment. There are many studies on osteoblast differentiation in normal medium (35,36). On the basis of these studies, we will carry out relevant research on whether miR-214-3p can promote osteogenesis in normal medium in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Both GO and nitrogen-doped graphene (N-Gr) have low cytotoxic effects and injury of oxide stress for DFPCs, indicating they are valuable candidates for DFPCs scaffolds [114]. In addition, NS+F revealed a similar effect on providing a suitable microenvironment and enhancing DFPCs osteogenesis [113]. Moreover, TiHA can induce osteogenic differentiation of DFPCs even in the absence of exogenous factors owing to their chemical and topographical properties [112].…”
Section: Dfpcs and Scaffoldsmentioning
confidence: 99%